Analysis and Ideas for Improved Routing in MANET - Kumar, Josh; Kathirvel, A. (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Mobile Ad hoc NETwork is a collection of mobile nodes connected with each other without any centralized infrastructure support. In MANET, every node acts as a router, thereby forwards the packet to other nodes through the best route possible. The cooperation of all other nodes is very essential for a node to transfer data to its desired destination. Throughput is a major factor that determines the health of any network including MANET and there can be many reasons that can disrupt the throughput. In this paper we deal with two prime reasons that may reduce the throughput in a MANET. The first reason is that, if a node behaves selfishly and utilizes the path only for forwarding its own packet, then the packets from other nodes will be dropped and the throughput will gradually get reduced. The second reason for reduction in throughput is the phenomenon called fading, which causes signal attenuation. This phenomenon creates path loss temporarily, during which the packet loss increases and the throughput takes a major hit. Removing such nodes from the network on the basis of doubt about its packet forwarding nature and ability will eventually weaken the network strength. Neglecting the original best route will also reduce the quality of the network. Both the cases of selfishness and fading can be normalized by switching over to an alternate path and coming back to the same route after a short period of time. Thereby the quality as well as the quantity of nodes involved in the network can be maintained. In this paper we have also introduced an innovation called helper nodes which will also help in the formation of alternate path and will very well neutralize the ill effects caused due to selfishness and fading.